LIMK2 Is a Novel Prognostic Biomarker and Correlates With Tumor Immune Cell Infiltration in Lung Squamous Cell Carcinoma - Su, Yongcheng; Xu, Beibei; Shen, Qianwen; Lei, Ziyu; Zhang, Wenqing; Hu, Tianhui (Frontiers in Immunology, 2022)
Previous research found that LIMK2 expression correlated with a poor prognosis in many cancers. However, its role in lung squamous cell carcinoma (LUSC) has not yet been clarified. Our study aimed to clarify the role of LIMK2 in LUSC prognosis prediction and explore the relationship between LIMK2 and immune infiltration in LUSC. In this study, we first analyzed the expression level and prognostic value of LIMK2 across cancers. Subsequently, we explored the association of LIMK2 expression with immune infiltrating cells and immune checkpoints. our study found that LIMK2 was highly expressed and positively associated with the overall survival of LUSC. Moreover, our study further indicated that LIMK2 expression was significantly negatively correlated with immune cell infiltration and immune checkpoints in LUSC. Finally, we confirmed upstream regulatory noncoding RNAs (ncRNAs) of LIMK2, and the PVT1 and DHRS4-AS1/miR-423-5p/LIMK2 regulatory axes were successfully constructed in LUSC. Put together, LIMK2 is a novel prognostic biomarker and correlates with tumor immune cell infiltration in LUSC, and the expression of LIMK2 is regulated by the PVT1 and DHRS4-AS1/miR-423-5p axes.